The braid group: redefining - Nasution Mahyuddin K M (MATEC Web of Conferences, 2018)
The role of the braid group constitutes one of the invariant measurements. Through the classification of braids formed several parts of the braid group, but does not computationally distinguish them. Some characteristics have been expressed to give the features to a braid in braid group based on redefining relation between braid group and permutation group.